Prague-Freedom of Mind and Spirit. (Kanopy Streaming, 2015)
In this famously beautiful city, travel the royal road from the ceremonial Powder Tower to Prague Castle. Pause at the Courtyard of the Merchants and the spectacular Old Town Square, with its medieval city mansions, Town Hall, and extraordinary astronomical clock. Savor the magical atmosphere of Prague's rich architectural landscape.